Jet-injection assisted photodynamic therapy for superficial and nodular basal cell carcinoma: a pilot study - Lavin, Leore; Erlendsson, Andrés M.; Aleissa, Saud; Aleisa, Abdullah; Menzer, Christian; Dusza, Stephen; Cordova, Miguel; Alshaikh, Hesham; Shah, Rohan; Pan, Alexander; Ketosugbo, Kwami; Hosein, Sharif; et al. (Lasers in surgery and medicine, 2024)
Background Photodynamic therapy (PDT) with topical δ-Aminolevulinic acid (ALA) has efficacy in treating basal cell carcinoma (BCC) but is limited by incomplete penetration of ALA into the deeper dermis. This prospective open-label pilot trial investigated the safety and efficacy of photosensitizer jet injection for PDT (JI-PDT) for BCC treatment. It was performed with 15 patients (n = 15) with histologically confirmed, untreated, low-risk nodular BCCs at a single institution. Methods For the intervention, JI-PDT patients (n = 11) received two sessions of jet-injected ALA with PDT separated by four to 6 weeks. To further understand treatment technique, another group of patients (n = 4) received jet-injected ALA followed by tumor excision and fluorescence microscopy (JI-E). Treatment tolerability was assessed by local skin responses (LSR) score at five distinct time intervals. Fluorescence microscopy assessed protoporphyrin IX penetration depth and biodistribution within the tumor. At the primary endpoint, tumor clearance was evaluated via visual inspection, dermoscopy and reflectance confocal microscopy. Postinjection and postillumination pain levels, and patient satisfaction, were scored on a 0−10 scale. Results Fifteen participants with mean age of 58.3, who were 15/15 White, non-Hispanic enrolled. The median composite LSR score immediately after JI-PDT was 5 (interquartile range [IQR] = 3) which decreased to 0.5 (IQR = 1) at primary endpoint (p < 0.01). Immunofluorescence of excised BCC tumors with jet-injected ALA showed photosensitizer penetration into papillary and reticular dermis. Of the 13 JI-PDT tumors, 11 had tumor clearance confirmed, 1 recurred, and 1 was lost to follow-up. 1/11 patients experienced a serious adverse event of cellulitis. 70% of patients had local scarring at 3 months. Patients reported an average pain level of 5.6 (standard deviation [SD] = 2.3) during jet injection and 3.7 (SD = 1.8) during light illumination. Conclusions Jet injection of ALA for PDT treatment of nodular low-risk BCC is tolerable and feasible and may represent a novel modality to improve PDT.
Gesehen am 02.12.2024